Newer indications of tranexamic acid in dermatology beyond melasma: a review - Astha Arora; Mala Bhalla (Wolters Kluwer Medknow Publications, 2022)
Tranexamic acid (TXA) is an antifibrinolytic agent approved for use to control bleeding during surgery and after trauma. It has been used in dermatology as a therapeutic and prophylactic agent in angioedema since 1970s but its recently discovered role in melasma has made it the current molecule of interest. At present TXA is being widely researched for multiple indications in view of its role in reducing melanogenesis and angiogenesis in skin. Various case reports and clinical trials have been published over the last few years describing its role in postinflammatory hyperpigmentation, dermal melanosis, rosacea, telangiectasia, and even as an antiaging agent. We present this review here summarizing the various publications for the aforementioned indications.